"Metade vale mais que tudo": a sabedoria hesiódica na República de Platão - Camila do Espirito Santo Prado de Oliveira (2013)
This work develops three hypothesis: 1. The study of the Hesiod´s presence in Plato's work is relevant to understanding of his own thought ; 2. Plato engages specifically with Works and Days in the Republic, one hallmark of this is the quote of verse 40 of the poem in 466c of the dialogue; 3. The conquest of Hesiod´s inheritance by Platonic philosophy requires the search of the foundation of the wisdom of the Boeotian poet, wich the philosopher determines like knowledge of the Idea of the Good. To accomplish the first task, after a brief literature review, it is exposed one series of allusions to Hesiod in Plato. It is evident, from there, that Hesiod is an important presence in the dialogues, being cited in the most part of Plato´s work. Betting on the second and main hypothesis of this thesis, we read Republic IV, with the focus points in the contact between this work and Works and Days, aiming in the construction of all the senses that allow us to interpret the hesiodic verse quoted by Plato: "half worth more than everything". The third hypothesis, developed by reading the steps of Books V and VI of the Republic in which it defines the figure of the philosopher-king, and his own knowledge - maintains that philosophy, taking a step further in relation to wisdom Hesiodic, grounds it. If the Idea of Good determines the course of any action that allows things being what they are, so, to know it means to see and follow the ordering that makes each one what it is, in its multiple connections with others. It is why the philosopher is the ruler: because the activity of philosophizing is to make visible the structure of the entire city and soul that needs to be saved. If, in Hesiod´s poetry, virtue is, guided by the measure of all, honors the work that is your own, in the Republic, the traditional discourse, to be properly performed, requires to explicit its foundation, the Good, which, however, as measure of the measures, transcends each measure, being the principle of determining any measure.